A comparative analysis of statutory remedy under the restitutio in integrum principle for contracts involving minors in Malaysia, England and Wales / Mohd Safri Mohammed Na’aim ... [et al.] - Mohammed Na’aim, Mohd Safri; Mohamad Hashim, Haswira Nor; Shaari@ Mat Saman, Nurulhasni; Jaiman, Cartaz Ummu Syawaeda; Abd Jamal, Jusniza (Universiti Teknologi MARA, Sabah, 2024)
This paper reports the findings of a study on the application of the principle of restitutio in integrum as a form of statutory remedy for void contracts involving minors. Within the Common Law legal system in Malaysia, England and Wales, the legal capacity to enter into a contract has been codified as one of the elements of a valid contract. Section 11 of the Malaysian Contracts Act 1950 (Act 136) (CA 1950) explicitly requires age of majority as one of the conditions of a competent person, whereby the legal effect of contracts with minors is void. The research problem stems from the apparent lack of legislative protection for adults who fairly entered into contracts with minors under the CA 1950. While restitution resulting from a void contract can be sought under section 66 of the CA 1950, the relief under the section can only be invoked if the agreement is “discovered to be void”. The research endeavours to overcome the unfairness suffered by the adult contracting party through the legislative reform of restitution in contracts involving minors. To achieve this aim, the research conducted a comparative legal analysis of the legislation on contracts entered into by minors between Malaysia, England and Wales. The samples for analysis are the Minors’ Contracts Act 1987 (MCA 1987), case law, textbooks, journal articles, and scholarly writings related to this area. The primary and secondary legal resources were analysed using doctrinal and content analysis to compare the legal position on restitution in a minor’s contract between both jurisdictions. The research proposed that section 66 of the CA 1950 is amended by taking into account section 3 of the MCA 1987, which leaves the issue of restitution to the discretion of the court based on justice and fairness. It is anticipated that the amendment would protect adults who have fairly entered into agreements for non-necessaries with minors in Malaysia.